2014
DOI: 10.1186/preaccept-3072014071278914
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mapping of the MHC transactivator CIITA using an integrated ChIP-seq and genetical genomics approach

Abstract: Background: The master transactivator CIITA is essential to the regulation of Major Histocompatibility Complex (MHC) class II genes and an effective immune response. CIITA is known to modulate a small number of non-MHC genes involved in antigen presentation such as CD74 and B2M but its broader genome-wide function and relationship with underlying genetic diversity has not been resolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In addition, an eGWAS performed on blood from cohorts of healthy women and breast cancer survivors showed an association between ten HLA genes ( HLA-C , HLA-E , HLA-F , HLA-G , HLA-H , HLA-DPB1 , HLA-DQA1 , HLA-DQB1 , HLA-DRB3 , HLA-DRB4 ) and SNPs in 100 genes located on human chromosome 6 [ 37 ]. In particular, CIITA has been identified as a master trans -activator, with an essential role in initiating transcription of MHC class II genes in human stimulated B cells and monocytes [ 38 ]. However, our eGWAS did not generate any evidence of CIITA acting as a master regulator, despite the presence of one CIITA -related SNP on the array.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an eGWAS performed on blood from cohorts of healthy women and breast cancer survivors showed an association between ten HLA genes ( HLA-C , HLA-E , HLA-F , HLA-G , HLA-H , HLA-DPB1 , HLA-DQA1 , HLA-DQB1 , HLA-DRB3 , HLA-DRB4 ) and SNPs in 100 genes located on human chromosome 6 [ 37 ]. In particular, CIITA has been identified as a master trans -activator, with an essential role in initiating transcription of MHC class II genes in human stimulated B cells and monocytes [ 38 ]. However, our eGWAS did not generate any evidence of CIITA acting as a master regulator, despite the presence of one CIITA -related SNP on the array.…”
Section: Discussionmentioning
confidence: 99%
“…The high specificity of NLRC5 for a small number of phylogenetically related MHCI genes is strikingly similar to that of CIITA, for which ChIP-on-microarray experiments have revealed high selectivity for genes involved in MHCII-mediated antigen presentation [ 12 ]. Although recent ChIP-seq experiments have suggested that there are other CIITA-occupied sites in the genome [ 27 ], their functional relevance remains to be demonstrated. The extremely focused activity of NLRC5 and CIITA sets them apart from other transcription factors and transcriptional coactivators, which typically regulate hundreds or thousands of genes and exhibit much more diverse and pleiotropic functions; these two NLRs are instead specialized for the expression of only few phylogenetically and/or functionally related genes, representing a novel type of highly dedicated transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%
“…By applying more stringent selection, 53 and 20 of the above loci could be found in three to four or all datasets, respectively. While this work was in progress, an independent CIITA ChIP-seq on human B cells was published ( 69 ). In that study, only the Diagenode antiserum was used and 843 CIITA loci were identified, which had significant overlap with the data presented herein.…”
Section: Discussionmentioning
confidence: 99%